2018
DOI: 10.1080/13607863.2018.1517727
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of self and proxy quality of life ratings for people with dementia and their carers: a European prospective cohort study

Abstract: Objectives: To identify correlates of self-rated and proxy-rated quality of life (QoL) in people with dementia on (i) a dementia-specific and (ii) a capability-wellbeing QoL measure at baseline and 12month follow-up, and to consider such factors in the context of QoL intervention development. Method: Prospective clinical and demographic data were collected from 451 community-dwelling dyads (mild-moderate dementia) across eight European countries. QoL was measured using the QOL-AD and the ICECAP-O. Multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 49 publications
3
30
1
Order By: Relevance
“…Since it is a key predictor (indeed a component) of quality of life, the study of RQ allows us to better understand this broader and multifaceted construct. The complex determinants of quality of life were analysed in another Actifcare paper …”
Section: Discussionmentioning
confidence: 99%
“…Since it is a key predictor (indeed a component) of quality of life, the study of RQ allows us to better understand this broader and multifaceted construct. The complex determinants of quality of life were analysed in another Actifcare paper …”
Section: Discussionmentioning
confidence: 99%
“…Care receivers adhering to the specified criteria ("Appendix 1") and their informal carers were invited to complete the questionnaires, available in seven different languages. For all measures, including the ICECAP-O, nationally validated versions were used, or, if not available, the measure was translated, back translated and pilot tested following a translation protocol [21][22][23]. The data collection consisted of different parts.…”
Section: Methodsmentioning
confidence: 99%
“…Future research should enhance recent reviews [37,41] and conduct a meta-analysis of different QoL measures completed by different raters over time, in order to establish which are most meaningful and suitable for use. One recent narrative review concluded that self-report and proxy-report DEMQOL and EQ-5D-5L should be used [15].…”
Section: Limitationsmentioning
confidence: 99%